The history behind ALS type 8: from the first phenotype description to the discovery of VAPB mutation - Luiz Eduardo NOVIS; Mariana SPITZ; Hélio A. G. TEIVE (Arquivos de Neuro-Psiquiatria)
ABSTRACT Over the past 68 years, the Finkel type late-onset adult autosomal dominant spinal muscular atrophy (SMA) that is allelic with amyotrophic lateral sclerosis-8 (ALS8) gained a genotype-phenotype correlation among the motor neuron diseases through the work of groups led by Zatz and Marques Jr.